The Creation of New Place and Space in Toni Morrison’s Paradise: Collective Identity of “Ruby” Vs. Self-identity of “the Convent” - LADAJALI, Samira; MEBARKI, Fatima; GUELLIL, Assia (Faculty of Letters and Foreign Languages Department of English, 2019)
This dissertation approaches the study of Toni Morrison’s ‘Paradise’, aims at showing that ‘the convent’ was more successful than ‘Ruby’ in the construction of identity through the creation of new place and space. The two African American communities used the creation of new space and place as a way to escape racism and discrimination. On the one hand, ‘Ruby’ emerges as Toni refers to “black town that worth the pain”. It is characterized by geographical isolation and separateness. Consequently, it falls prey to its solitude. On the other hand, ‘the Convent’ is an open community that welcomes all believes without judgment. ‘The Convent’, thus, adopted the values of freedom and equality which make it a confront zone and a perfect paradise. Through this dissertation we followed three methods, the descriptive, the comparative and the analytical method. Throughout this study, we point out that the convent women succeed to form their self-identity by the creation of new place and space. However, Ruby fails to reconstruct its collective identity because of the creation of an isolated place, which prevents Ruby from development and continuity